New approach to design of ceramic/polymer material compounds. Issue 1 (March 2016) - Todt, A; Nestler, D; Trautmann, M; Wagner, G
Abstract: The damage tolerance of carbon fibre-reinforced ceramic-matrix composite materials depends on their porosity and can be rather significant. Complex structures are difficult to produce. The integration of simple geometric structures of ceramic-matrix composite materials in complex polymer-based hybrid structures is a possible approach of realising those structures. These hybrid material compounds, produced in a cost-efficient way, combine the different advantages of the individual components in one hybrid material compound. In addition the individual parts can be designed to fit a specific application and the resulting forces. All these different advantages result in a significant reduction of not only the production costs and the production time, but also opens up new areas of application, such as the large-scale production of wear-resistant and chemically inert, energy dampening components for reactors or in areas of medicine. The low wettability of the ceramic component however is a disadvantage of this approach. During the course of this contribution, different C/C composite materials with a specific porosity were produced, while adjusting the resin/hardening agent-ratio, as well as the processing parameters. After the production, different penetration tests were conducted with a polymer component. The final part of the article is comprised of the microstructural analysis and the explanation of the mechanical relationships.